Facilities and Work Behavior of Nurses on Patient Satisfaction through Nurse Performance at Pasir Putih Health Center - umar wiranto; Rasniah Sarumi; Dian Rosmala Lestari; Abdul Sila (Journal of sciences and health, 2022)
Background: The low rate of patient satisfaction will have an impact on the development of health centers or hospitals. For patients who are dissatisfied with the service received, the patient will move to another facility that provides better service. The purpose of this study was to determine the effect of the facilities and work behavior of nurses on patient satisfaction through the performance of nurses at the Pasir Putih Health Center.Methods: This type of research is an analytical survey with a cross-sectional study approach, the sample consists of 287 respondents, used simple a random sampling technique. Data were collected through observation, interviews, and questionnaires. Data analysis was carried out using path analysis, which is a development technique of multiple linear regression. Results: The results showed that the facilities p = 0,008, nurse behavior p = 0,020, nurse performance p = 0,000. R Square value 0,413. This means that the influence of facilities, behavior on nurse performance through patient satisfaction is 41,3%. Path analysis shows the effect of facilities (0,134) and nurses' work behavior (0,147) on patient satisfaction through nurse performance. There is a direct effect of nurse behavior on patient satisfaction (0,116) and there is an indirect effect between facilities and nurse performance on patient satisfaction (0,161).Conclusion: there is an effect of facilities and work behavior of nurses on patient satisfaction through nurse performance. It is suggested to the Pasir Putih Health Center to maintain and improve the work behavior of nurses towards patients to encourage an increase in the image and commitment of patients to continue using the Pasir Putih Health Center in the future. Keywords: Facilities, work behavior, nurses, patient satisfaction, performance